Impact of chemotherapy on humoral and cellular immune responses to COVID-19 vaccination in patients with solid tumors - Favalli, Andrea; Patelli, Giorgio; Gruarin, Paola; Gobbini, Andrea; Pesce, Elisa; Mariano, Sara; Bombaci, Mauro; Vincenti, Francesca; Donnici, Lorena; Marchese, Silvia; Piscazzi, Daniele; Amatu, Alessio; et al. (Frontiers in Immunology, 2025)
IntroductionDespite SARS-CoV-2 pandemic has subsided, vaccine response profiling in patients with cancer remains critical. MethodsWe longitudinally assessed humoral and cellular immunity in adults with solid tumours treated with chemotherapy (ChT) or non-ChT regimens after two mRNA vaccine doses plus booster, compared with vaccinated cancer-free controls, naturally infected (convalescent) subjects including both patients with cancer and cancer-free individuals, and unvaccinated/uninfected individuals with or without cancer as a baseline reference. ResultsAnti-Spike IgG titres matched cancer-free controls, but anti-RBD titres and neutralising activity were consistently lower in cancer post-vaccination, most markedly with ChT, and declined faster over 4-6 months. Boosters restored IgG, yet gains were smaller in ChT recipients. Cellular analyses revealed sustained and booster-enhanced Spike-specific B cells in all groups; however, ChT exposure was associated with reduced CD27 expression on these cells, suggesting impaired activation and memory maturation.DiscussionThese findings support tailored immune monitoring and vaccination strategies in oncology and identify CD27 downregulation as a novel B-cell dysfunction detected by high-dimensional immunophenotyping.